2022
DOI: 10.1155/2022/3336257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hydropower Generation and Reservoir Operation under Climate Change from Kesem Reservoir, Ethiopia

Abstract: Climate changes significantly cause the precipitation deficiency and in turn reduce the inflow amount in reservoir affecting hydroelectric power generation. The primary objective of this study was to evaluate hydropower generation and reservoir operation under climate change from Kesem reservoir. Recent Representative Pathway (RCP) scenarios were used to evaluate the impact of climate change on power generation. Power transformation equation and variance scaling approach were amalgamated to adjust the bias cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Advances in Meteorology (i) Estimating and flling missing data: Inverse distance or weighting method is most commonly used for the estimation of missing precipitation [40][41][42]. Rainfall data of interpolation using inverse distance weighting (IDW) can obtain more accurate results [43][44][45][46]. Te rainfall at a station was estimated as a weighted average of the observed rainfall at the neighboring stations.…”
Section: Bias Correction Of Climaticmentioning
confidence: 99%
“…Advances in Meteorology (i) Estimating and flling missing data: Inverse distance or weighting method is most commonly used for the estimation of missing precipitation [40][41][42]. Rainfall data of interpolation using inverse distance weighting (IDW) can obtain more accurate results [43][44][45][46]. Te rainfall at a station was estimated as a weighted average of the observed rainfall at the neighboring stations.…”
Section: Bias Correction Of Climaticmentioning
confidence: 99%
“…The daily and monthly power created from the simulation model output throughout the course of the entire year of analysis shows that there is significant daily and monthly power generation volatility caused by considerable changes in inflow and outflow [ 5 ]. During the wet season, the inflow to the reservoir is very high and the release increased to generate more power, and during dry season, inflow is less and generates less power.…”
Section: Resultsmentioning
confidence: 99%
“…Water resources management is the backbone for the economic growth of a developing country [ [1] , [2] , [3] , [4] , [5] ]. The day-to-day activities of all human beings have been deeply connected with water which can be compensated from reservoirs built on streams or rivers to fulfil during the rainy season and meet various demands during dry seasons [ [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%
“…However, 83% of the population do not have access to electricity [ 16 ]. Therefore, expanding hydropower projects and electricity generation are two of the four pillars of Ethiopia's Climate Resilience Green Economy (CRGE) [ 17 , 18 ]. Therefore, the Ethiopian government has planned to generate 22.14 Gigawatt (GW) of hydropower by the end of the 2030s [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the finding, the energy production of the GERD reservoir exhibited both a rising and a declining signal at the end of the 2050–2059 and 2090–2099 centuries, respectively, whereas the power capacity of the GIBE–III hydropower showed an increasing signal. Another study by Mirani et al [ 18 ] revealed that the hydropower potential of Kessem reservoir in Ethiopia showed a declining trend under the influence of climate. Adera and Alfredsen [ 16 ] also investigated how the Tekeze hydropower reservoir might perform under the influence of climate change.…”
Section: Introductionmentioning
confidence: 99%